The Role of Religion in the Lives, Agency, and Activism of Domestic Worker Leaders - Susheela Mcwatts (African Journal of Gender and Religion (AJGR))
One of the key themes that emerged when researching domestic worker leader activism for my doctoral study, was the role of religion in developing agency among domestic worker leaders and religion’s influence on their need to serve their constituents. Although Paulo Freire argues that traditional reli-gion can be fatalist and functions to preserve the status quo, the ability of reli-gious institutions to mobilise women is not a new phenomenon, nor is reli-gion’s role in the liberation from other forms of oppression. In this article, I explore the role that religious institutions such as churches have played in shaping the activist identities of domestic worker leaders whom I have inter-viewed, and the centrality of religion in these women’s lives, against a back-drop of their own life circumstances, the employers they worked for, and the larger political climate in their own countries.